Hybrid Solidarity and Ritual Resistance among the Parmalim Indigenous Belief Community in Indonesia - Harisan Boni Firmando; Elvri Teresia Simbolon; Roida Lumbantobing (Khazanah Sosial, 2026)
This study examines how the Parmalim community, an indigenous Batak Toba belief system, maintains social cohesion and develops institutional adaptation amid structural state discrimination against indigenous belief identities. The study is important because indigenous belief communities in Indonesia continue to experience administrative, social, and political marginalization within religion-state relations. This research employs a qualitative approach using an embedded case study design that combines ethnographic methods and critical discourse analysis to understand ritual practices, social solidarity, and institutional adaptation within the Parmalim community in North Sumatra. Data were collected through twelve months of participant observation, semi-structured interviews, focus group discussions, and document analysis concerning ritual practices, Ugamo Malim organizational structures, and state policies related to the recognition of indigenous beliefs, and were analyzed thematically using Émile Durkheim’s theory of solidarity. The findings reveal that mechanical solidarity within the Parmalim community is maintained through collective rituals such as Marari Sabtu and Sipaha Lima, which strengthen collective identity while simultaneously functioning as forms of symbolic resistance against dominant religious structures. At the same time, organic solidarity develops through the establishment of formal organizations, legal advocacy, and collaboration with civil society networks to pursue recognition of indigenous belief rights. These findings indicate that mechanical and organic solidarity do not operate linearly but coexist simultaneously in the form of “hybrid solidarity.” The study highlights the importance of understanding ritual practices and institutional adaptation as strategies used by indigenous communities to sustain their social and political existence within pluralistic societies. This research also extends the Durkheimian framework by demonstrating that social solidarity in indigenous communities cannot be separated from state power relations and postcolonial dynamics. The originality of this study lies in the development of the concepts of “hybrid solidarity” and “ritual resistance” to explain the relationship between cultural practices, social cohesion, and the struggle for recognition among indigenous belief communities in Indonesia.